Perceived social and educational problems encountered by students with hearing impairment in inclusive schools in federal capital territory, Abuja (2019)
Inclusion of students with hearing impairment into regular schools came as education policies in Nigeria so that long tends of exclusion of students with hearing impairment from school get resolved. The rationale behind inclusion was not only academic gain but also the development of the social relation of students with hearing impairment with members of the society. This study examined the perceived social and educational problem encountered by students with hearing impairment in inclusive schools in Federal Capital Territory (FCT), Abuja. Three research questions were generated for the study. The descriptive survey design was adopted for the study. One hundred (100) students with hearing impairment were drawn from ten (10) Inclusive schools in FCT, Abuja. One instrument of two parts was used for the purpose of data collection. Descriptive and Inferential statistics were used for the data analysis. The results showed that students with hearing are confronting various challenges in the schools such as low self-esteem, the inadequacy of teaching and learning materials and the lack of attention from school personnel. Also, the students with hearing impairment do not a significant difference in challenge they faced based on age and gender.